PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA TANGRAM TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS I SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study aimed to analyze the effect tangram-assisted Problem Based Learning (PBL) on first grade elementary students mathematical critical thinking skills. This study employed a quantitative method with a one-group pretest posttest design. The participants were 20 first-grade students of SDIT Lampu Iman Karawang. Data were collected through a test consisting of six essay items developed based on indicators of critical thinking skills. The data were analyzed using descriptive statistic, the Shapiro-Wilk normality test, paired sample t-test, and N-gain score analysis. The results showed that the mean pretest score was 64,75 and increased to 88,30 in the posttest. The normality test indicated that both pretest and posttest data were normaly distributed. Furthermore, the pretest and posttest scores exhibited a significant difference, as evidenced by the paired sample t-test results (p < 0,001), indicating a significant difference between pretest and posttest scores. Therefore, the Problem Based Learning model assisted by tangram media had a significant effect on students’ mathematical critical thinking skills.